2011
DOI: 10.1080/13825585.2011.609882
|View full text |Cite
|
Sign up to set email alerts
|

Age-related effects of blood pressure on everyday cognitive function in community-dwelling women

Abstract: These results support that blood pressure may be an important predictor of everyday cognitive abilities in older age. Potential implications for real-world functioning are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…The presence of a relationship between high blood pressure and cognitive impairment appears to be confirmed by studies comparing hypertensives and normotensives. In these studies, people with hypertension showed a higher decline of global cognitive functioning [72,75,88] than normotensive.…”
Section: Blood Pressure and Global Cognitive Functioningmentioning
confidence: 97%
See 2 more Smart Citations
“…The presence of a relationship between high blood pressure and cognitive impairment appears to be confirmed by studies comparing hypertensives and normotensives. In these studies, people with hypertension showed a higher decline of global cognitive functioning [72,75,88] than normotensive.…”
Section: Blood Pressure and Global Cognitive Functioningmentioning
confidence: 97%
“…However, in some cases, studies showed inconsistent results. On the one hand, high blood pressure was associated with worse cognitive performance [41,67,68,72,73,78]. A poor performance was also associated with higher systolic blood pressure [43,48,62,66,69], or with higher diastolic blood pressure only [44,47].…”
Section: Blood Pressure and Global Cognitive Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…The Everyday Problem Solving (EPS) test consisted of eight interpersonal vignettes derived from previous literature [50, 66, 67] and applied in various older adult studies [46, 48, 51, 52, 57, 68]. Problems are “ill-structured” to allow for generation of multiple responses (e.g., “A person who lives alone wants to see her children more frequently.…”
Section: Methodsmentioning
confidence: 99%
“…Ill-structured measures rely more on response fluency demands in addition to functional crystallized knowledge [51]. Previous work revealed specific associations between low OBP and decreased performance on ill-structured everyday problems in older women [52]. The current study incorporated both ill- and well-structured tasks to broadly assess everyday cognition.…”
Section: Introductionmentioning
confidence: 99%